2018
DOI: 10.1016/j.stemcr.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

An Adeno-Associated Virus-Based Toolkit for Preferential Targeting and Manipulating Quiescent Neural Stem Cells in the Adult Hippocampus

Abstract: SummaryQuiescent neural stem cells (qNSCs) with radial morphology are the only proven source of new neurons in the adult mammalian brain. Our understanding of the roles of newly generated neurons depends on the ability to target and manipulate adult qNSCs. Although various strategies have been developed to target and manipulate adult hippocampal qNSCs, they often suffer from prolonged breeding, low recombination efficiency, and non-specific labeling. Therefore, developing a readily manufactured viral vector th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Interestingly, the total number of Sox2+ cells, composed of Type 1 and 2a NPCs, was relatively unaffected by rAAV, consistent with this population being largely quiescent (Figure 2 B,C). The fact that Sox2+ cells were mostly preserved in our experiments might explain why Type I cells are visualized in studies utilizing a large range of AAV titers, including titers greater than those reported here (Crowther et al, 2018;Kotterman et al, 2015;Ojala et al, 2018;Pulicherla et al, 2011;Song et al, 2012).…”
Section: A Developmental Window For Sensitivity To Raav-induced Toxicitymentioning
confidence: 71%
“…Interestingly, the total number of Sox2+ cells, composed of Type 1 and 2a NPCs, was relatively unaffected by rAAV, consistent with this population being largely quiescent (Figure 2 B,C). The fact that Sox2+ cells were mostly preserved in our experiments might explain why Type I cells are visualized in studies utilizing a large range of AAV titers, including titers greater than those reported here (Crowther et al, 2018;Kotterman et al, 2015;Ojala et al, 2018;Pulicherla et al, 2011;Song et al, 2012).…”
Section: A Developmental Window For Sensitivity To Raav-induced Toxicitymentioning
confidence: 71%
“…An additional alternative method is to deliver transgenes plus cleavably-linked fluorescent reporters using viral vectors that target expression to specific cell populations based on viral serotype or cell-specific promoters. For example, certain adeno-associated viruses show preference for infecting specific NSPC subclasses and can be used to manipulate gene function in adulthood after stereotaxic delivery (Crowther et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…2 B,C). The fact that Sox2+ cells were mostly preserved in our experiments might explain why Type I cells are visualized in studies utilizing a large range of AAV titers, including titers greater than those reported here (Crowther et al, 2018;Kotterman et al, 2015;Ojala et al, 2018;Pulicherla et al, 2011;Song et al, 2012).…”
Section: A Developmental Window For Sensitivity To Raav-induced Toxicitymentioning
confidence: 59%